Mechanical and Structural Properties of Fluorine-Ion-Implanted Boron Suboxide - Ronald Machaka; Bonex W. Mwakikunga; Elayaperumal Manikandan; Trevor E. Derry; Iakovos Sigalas; Mathias Herrmann (Advances in Materials Science and Engineering)
Results on a systematic study on the effects of ion implantation on the near-surface mechanical and structural properties of boron suboxide (B6O) prepared by uniaxial hot pressing are reviewed. 150 keV fluorine ions at fluences of up to 5.0×1016 ions/cm2 were implanted into the ultrahard ceramic material at room temperature and characterized using Raman spectroscopy, atomic force microscopy, and scanning electron microscopy with energy-dispersive X-ray spectroscopy. Evidence of ion-beam-assisted nucleation of novel clustered BxOyFz particles by ion implantation is revealed. In addition, obtained results also reveal that fluorine implantation into the B6O specimen leads to an overall degradation of near-surface mechanical properties with increasing fluorine fluence. Implications of these observations in the creation of amorphous near-surface layers by high-dose ion implantation are discussed in this paper.